Dealing with deontic modality in a termbase: the case of Dutch and Spanish legal language - Vanden Bulcke, Patricia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
In this article, we analyse, on the basis of comparable corpora (Dutch - Spanish) of the same legal genre, i.e. the Articles of Association, an aspect of cross-linguistic variation, namely the expression of deontic modality. We also examine the ways in which the findings of the study can be processed into a bilingual, translator-friendly legal termbase (JuriGenT). In doing so, we map out the asymmetry, which is mainly attributable to the use of tenses, and duly process this in the relevant term records, taking the view that the translator should be aware of the similarities and differences of their usage so as to be able to make well-considered translation decisions.